Cornelius a fable - Lionni, Leo 1910- (New York Knopf, 1994)
Cornelius, a crocodile who walks upright, sees things no crocodile has ever seen before.
"Originally published in hardcover by Pantheon Books in 1983"--T.p. verso.
Keywords: Crocodiles -- Juvenile fiction